THE GENRE-BASED APPROACH TO TEACHING WRITING REPORT TEXT - Lesnawati, Leni (2014)
This thesis reports the results of a study about the effectiveness of the Genre Based Approach in teaching writing Report text in one state junior high school in Subang, West Java. The study employed classroom action research that is commonly associated with qualitative research method. This study employed three cycles of action research covering a diagnostic phase in Cycle 1 and two therapeutic phases in Cycle 2 and 3. The data were collectedduring fourteen meetings through participant classroom observation, the documentation of students' Report texts and interview. The participant classroom observation was conducted while the class was in progress or immediately after each session. This observation was conducted in the classroom, the multi media room and in the library. This observation included handwritten brief notes and photographs. The documentation of students' Report texts was collected at the end of the teaching program. Only nine students' texts were analyzed in detail. The nine texts represented different levels of achievement: three texts from low achievers, three texts from mid achievers and three texts from high achievers. The interview was conducted in the last meeting after the teaching program in multi media room. Nine students were interviewed by using bahasa Indonesia.The data from classroom observation were analyzed based on students' behaviours and interactions that occurred during the teaching program relevant to the research questions. The data from the students documentary texts in various stages of the teaching cycle were analyzed based on Systemic Functional Linguistics in terms of Schematic Structure and Linguistic Features as developed by Halliday (1994). The data from interview were analyzed based on the central theme 1 about the way of the GBA in improving students' writing ability and the central theme 2 about students' responses toward the teaching of writing using the GBA. The results of the students' texts analyses revealed that the students showed considerable improvement in writing skills in terms of the schematic structure and linguistic features. It was found that the schematic structure of the texts suggests the students' improvement in constructing a successfully organized text. It was also found that the students could demonstrate their ability to use various linguistic resources to communicate effectively through the texts. The grammatical analyses of each element of the texts showed the students' development in composing the targeted text. The data from classroom observations and interviews showed that the students were aware of making progress in terms of writing skills. They also participated actively in the learning process and collaborated with the students and the teacher.Based on these findings, it is recommended that the Genre Based Approach can be implemented in English classrooms in Indonesia to improve students' ability in writing. The implementation of the GBA to teaching writing can be supported by classroom action research. English teachers should be encouraged to use these principles and do further research in teaching genres in various texts and in primary and secondary education. It is also recommended that the next related research should be conducted with a big number of participants within different context to get richer and more reliable data.